State of mood in futsal female athletes - Ramos, Ana Paula (2021)
Introduction: Futsal has been much studied in recent decades, and consequently its evolution has been dizzying, making professional athletes work at their limit most of the time, increasing the risk of injury and the rate of depression. This incessant search for results and yields, when added to the extra "field" factors, end up interfering with the athletes' psychological and physical performance, which can lead to high levels of stress and changes in the State of Mood Profile (PEH). Objective: To trace the mood profile of female futsal professional athletes for a whole season. Methods: This research is characterized by a quantitative, descriptive, comparative and epidemiological approach. We were intentionally selected female athletes from a professional futsal team, and an instrument was applied with the objective of tracing the epidemiological and demographic profile of these athletes' injuries, as well as the BRUMS scale assessing mood. Results: The sample involved 20 professional athletes. The values of the domains were within the expected for high performance athletes, similar to values already described in the literature in other sports. Conclusion: However it is clear that the humor profile of female futsal athletes evaluated is compatible with other modalities already studied. It is suggested that new studies be performed, with a greater number of athletes, allowing this data to contribute to the monitoring and optimization of yield.